Fog in western coastal ecosystems: inter-disciplinary challenges and opportunities with example concepts from the Pacific Northwest, USA - Dye, Alex; Rauschenbach, Sonya; de Szoeke, Simon; Igel, Adele L.; Jin, Yufang; Kim, John B.; Krawchuk, Meg A.; Maes, Kenneth; O’Neill, Larry; Paw U, Kyaw Tha; Samelson, Roger; Shaw, David C.; et al. (Frontiers in Environmental Science, 2024)
Coastal fog occurs along many of the world’s west coast continental environments. It is particularly consequential during summer when an increased frequency of fog co-occurs with the seasonal dryness characteristic of most west coast climate systems, for example, in the Pacific coast of North and South America, the southwestern African coast, and southern coastal Europe. Understanding coastal fog formation and effects has consequences for many disciplines, including the physical (e.g., atmospheric science, oceanography), biological (e.g., biogeography, ecophysiology), and socio-ecological realms (e.g., Indigenous cultural knowledge, public safety, economics). Although research practices differ across disciplines, they share many of the challenges needed to advance fog science. For example, coastal fog remains difficult to reliably monitor when, where, and why it occurs, which adds difficulty to understanding fog’s effects on all facets of the integrated coastal system. These shared challenges provide ripe opportunities for interdisciplinary collaboration, a template with past success in advancing fog-related science that can continue to have success in the future. In this perspectives review, we summarize the current status and frontiers of fog-related science from multiple disciplines, leveraging examples primarily drawn from the Pacific Northwest coastal region of the United States to show how interdisciplinary collaboration is needed to continue to advance our collective understanding of coastal fog formation and effects on west coast environments.